The Huawei and Snowden questions : Can electronic equipment from untrusted vendors be verified? Can an untrusted vendor build trust into electronic equipment? /: Can electronic equipment from untrusted vendors be verified? Can an untrusted vendor build trust into electronic equipment?. (2018) - Lysne, Olav
No abstract available